Phikud Navakot Modulates the Level of Pro-Inflammatory Mediators and the Protein Expression of SOD1 and 2 and the Nrf2/HO-1 Signaling Pathway in Rats with Acute Myocardial Infarction - Orapin Gerdprasert (2020)
© 2019 Orapin Gerdprasert et al. Phikud Navakot (PN) is nine major herbs in a famous traditional Thai recipe namely "Yahom Navakot" used to treat cardiovascular disorders. This study investigated the cardioprotective effects of PN formula on isoproterenol-induced myocardial infarction (IMI) in Sprague-Dawley rats. Forty-five rats were randomly divided into nine groups (n = 5 per group): the control, the IMI, the IMI + propranolol, the control or the IMI + PN formula (PN ethanolic extract at doses of 64, 127, or 255 mg/kg) by oroesophageal gavage for 28 days. The ST segment and serum troponin T levels were significantly increased in IMI rats. PN did not eliminate tissue necrosis, infiltration of inflammatory cells, or interstitial edema in IMI rats. All doses of PN decreased (p<0.001) serum TNF-α and IL-6 levels. PN (127 and 255 mg/kg) up-regulated (p<0.05) heme oxygenase (HO)-1 expression, whereas PN (255 mg/kg) significantly increased superoxide dismutase (SOD) 1 and 2 expression, compared with IMI rats. Nuclear factor erythroid 2-related factor 2 (Nrf2) and HO-1 expression significantly increased in IMI rats and IMI rats that received PN. PN formula possesses potential anti-inflammatory and antioxidant properties by modulating the levels of TNF-α, IL-6 and antioxidant enzymes. Our study reveals a novel cardioprotective effect of PN in IMI rats through the Nrf2/HO-1 signaling.